Evaluation of betelvine (Piper betle L.) cultivars in the gangetic alluvial plains of West Bengal, India - Munsi Nasir Imam, Anupam Pariari, (Journal of Spices and Aromatic Crops, 2012)
Evaluation of 14 cultivars of betelvine (Piper betle) in the gangetic alluvial plains of West Bengal indicated that there was wide variation among them for growth, yield and quality parameters. Cultivar Simurali Sanchi showed superior performance with respect to increment in vine length (145.37 cm during June to August), fresh (364.38 g) and dry weight (52.29 g) of 100 leaves (depetiolated) and total chlorophyll content in leaves (2.45 mg g-1 tissue). Leaf production was also maximum (58.56 vine-1 year-1) in cv. Simurali Deshi.